Stromal Vascular Fraction Cell Therapy for a Stroke Patient—Cure without Side Effects - Jaroslav Michalek; Alena Vrablikova; Karl Georg Heinrich; Zuzana Dudasova (Brain Sciences, 2019)
A 48-year-old male, who suffered from a stroke resulting in cerebellum damage and occlusion of the left vertebral artery, underwent stromal vascular fraction therapy. The clinical status of the patient was monitored by a modified Stroke Specific Quality of Life Scale before therapy and at 3, 9, 12, 18, 24, and 32 months after therapy. Three months after therapy, the patient felt a reduction in pain, vertigo, and fatigue. After 9 months, he was able to walk safely on his own. After 24 months, he was able to ride a bicycle. After 32 months, he felt completely healthy without any limitations or handicaps. Therefore, intravenous application of stromal vascular fraction cells represents a promising strategy for the treatment of patients after a stroke.